Technofeudalism illustrated by Trump’s Twitter suspension and Australia vs. Google and Facebook dispute - Bojić, Ljubisa; Zejnulahović, Damir; Janković, Miloš (Sociološki pregled, 2021)
Social media are becoming an indispensable communication tool today, including political communication. Therefore, technological companies running them have a great power. Every intervention they have in the public sphere may have far-reaching consequences. We will focus on two cases of the influence of technological companies on media, election and legislative processes as basic factors of democracy. We will consider the implications of the prohibition of Donald Trump’s use of Twitter, as well as the conflict of Australia’s media policy with Facebook and Google. We have reached the conclusion that in these cases technological companies took over the power that used to belong to the judicial and legislative branch of power, in terms of defining what hate speech, as well as media regulation is. Accordingly, this threatens the information system and sovereignty of the countries where these interventions are made. These events indicate that the world is entering a period of domination of technological companies, which may be called technocracy or technofeudalism. Further considerations should be directed towards defining social media as a public good that should be influenced by societies and not only technological companies as the owners of these communication platforms.